Doxorubicin-loaded human serum albumin nanoparticles overcome transporter-mediated drug resistance in drug-adapted cancer cells - Onafuye, Hannah; Pieper, Sebastian; Mulac, Dennis; Jr., Jindrich Cinatl; Wass, Mark N.; Langer, Klaus; Michaelis, Martin (Beilstein Journal of Nanotechnology, 2019)
Resistance to systemic drug therapy is a major reason for the failure of anticancer therapies. Here, we tested doxorubicin-loaded human serum albumin (HSA) nanoparticles in the neuroblastoma cell line UKF-NB-3 and its ABCB1-expressing sublines adapted to vincristine (UKF-NB-3rVCR1) and doxorubicin (UKF-NB-3rDOX20). Doxorubicin-loaded nanoparticles displayed increased anticancer activity in UKF-NB-3rVCR1 and UKF-NB-3rDOX20 cells relative to doxorubicin solution, but not in UKF-NB-3 cells. UKF-NB-3rVCR1 cells were re-sensitised by nanoparticle-encapsulated doxorubicin to the level of UKF-NB-3 cells. UKF-NB-3rDOX20 cells displayed a more pronounced resistance phenotype than UKF-NB-3rVCR1 cells and were not re-sensitised by doxorubicin-loaded nanoparticles to the level of parental cells. ABCB1 inhibition using zosuquidar resulted in similar effects like nanoparticle incorporation, indicating that doxorubicin-loaded nanoparticles successfully circumvent ABCB1-mediated drug efflux. The limited re-sensitisation of UKF-NB-3rDOX20 cells to doxorubicin by circumvention of ABCB1-mediated efflux is probably due to the presence of multiple doxorubicin resistance mechanisms. So far, ABCB1 inhibitors have failed in clinical trials probably because systemic ABCB1 inhibition results in a modified body distribution of its many substrates including drugs, xenobiotics, and other molecules. HSA nanoparticles may provide an alternative, more specific way to overcome transporter-mediated resistance.
Keywords: ABCB1; cancer; doxorubicin; drug resistance; human serum albumin; nanoparticles; transporter